The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1136/archdischild-2016-311808
|View full text |Cite
|
Sign up to set email alerts
|

Impact of functional somatic symptoms on 5–7-year-olds' healthcare use and costs

Abstract: Impairing FSS in children aged 5-7 years is a predictor for the child's future primary healthcare use. More research on complex predictive models is needed to further explore the clinical significance of these results, and to contribute to the underpinning of early interventions towards impairing FSS in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…To our knowledge, only one previous study has investigated the association between non-specific health complaints and future health care use. This study found higher healthcare use in Danish children with functional somatic symptoms at the age of 5-7 years 29 . Functional somatic symptoms are comparable to non-specific health complaint, except that the former primarily refers to medically unexplained somatic complaints.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…To our knowledge, only one previous study has investigated the association between non-specific health complaints and future health care use. This study found higher healthcare use in Danish children with functional somatic symptoms at the age of 5-7 years 29 . Functional somatic symptoms are comparable to non-specific health complaint, except that the former primarily refers to medically unexplained somatic complaints.…”
Section: Discussionmentioning
confidence: 49%
“…Given that health behavior is established in childhood and adolescence, it seems relevant to investigate how self-rated health and the experience of frequent non-specific health complaints in youth affect the contact pattern to primary health care over time [21][22][23][24] . The few existing studies in this area have mainly been cross-sectional 7,[25][26][27][28][29] .…”
mentioning
confidence: 99%
“…FSS in children and adolescents are associated with increased societal costs including extensive health care visits [98,99], school absence and parental absence from work [100]. Considering the suggested clinically relevant improvements in self-reported physical health and the high treatment satisfaction rated by the adolescents and parents and as observed in a good adherence rate, AHEAD may have the potential to improve quality of life and reduce illness-related impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The experience of somatic symptoms, such as gastrointestinal pain, headache, back pain and tiredness, is common in the general population [ 1 , 2 ]. Somatic symptoms are expensive in terms of direct costs for health care but also in a wider societal perspective due to decreased productivity [ 3 , 4 ]. Research over the two past decades has documented that somatic symptoms are also common in community-based samples of children and adolescents, particularly among girls [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%